Peningkatan Kesadaran Hukum terhadap Perkawinan Tidak Dicatatkan di Majelis Taklim Darussalam Desa Padang Lampe Kabupaten Pangkep - Jasmaniar Jasmaniar; Sutiawati Sutiawati (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This community service activity aims to provide knowledge and increase public legal awareness of the legal consequences of marriage not being registered, because there are still many marriages that are only carried out based on religious law but are not registered, causing various problems. This activity was carried out through legal counseling at the Darussalam Taklim Council, Padang Lampe Village, Pangkep Regency. As a result of this activity, participants understand the reasons for marriages to be registered and the legal consequences if marriages are not registered.